PERANCANGAN SISTEM INFORMASI PENGENALAN FENOMENA ALAM BERBASIS ANIMASI SECARA ONLINE (Studi Kasus : Badan Meteorologi Klimatologi Dan Geofisika) - Khasanah, Khasanah (Rang Teknik Journal, 2019)
The information system introduction of natural phenomenon defined as systems that convey information about the occurrence of natural phenomena. Problems that occur at this time is the delivery of information about natural phenomena only briefly obtained by the print or broadcast media. The problem solved by trying to build an information system design introduction of natural phenomena based online animations are developed using the prototype method. Animation presented in this information system is the chronological occurrence of a natural phenomenon while the system information of the website as a medium of information delivery. This system is expected to be a tool to facilitate the delivery of information about natural phenomena well anywhere and anytime as well as make it easier to add knowledge about the natural phenomena that occur.